Analysis of the Analytical Hierarchy Process Method to Prioritize the Development of Industrial Areas - Ricky Virona Martono (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
The research analyzes the steps in prioritizing several alternative Industrial Estates among various provinces uses the Analytical Hierarchy Process (AHP), which provides an assessment in the form of criteria weights for each alternative according to existing criteria. The criteria used to prioritize the location of these Industrial Estates are based on Presidential Decree No. 26 of 2012 concerning the Blueprint for the Development of the National Logistics System, namely: Port Capacity, Provincial Minimum age, and Economic Growth Rate. In the beginning we give relative weight to each criterion in determining Industrial Areas based on information from the Investment Coordinating Board. This weighting is useful for creating a priority order for each criterion, and then continuing with calculating the Adjusted Matrix and Consistency Ratio. The same steps are applied by giving relative weights between the criteria for each alternative Industrial Area, which is the weighting is carried out according to a comparison of quantitative and qualitative data for each Industrial Area. The final step is to use the Original and Adjusted Matrix to multiply all the weights of the alternatives and their criteria. The calculation results indicate that the industrial estate in Central Sulawesi is the top priority for development, while the other alternative locations need to address existing deficiencies before being designated as major industrial estates. Based on the AHP analysis, Central Sulawesi is identified as the most favorable location for industrial estate development, while North Maluku and West Papua require further improvements to meet the criteria.